PENGARUH PUPUK ORGANIK CAIR URINE MANUSIA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN GAMBAS (Luffa acutangula L. Roxb) - Kamelia Dwi Jayanti; Syahril A Kadir (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2020)
Luffa is one of the most popular vegetables and has a high nutritional value. Organic fertilizer can increase plant growth and yield, also can increase soil fertility without side effects such as inorganic fertilizer. One of the materials that is abundantly available and can be obtained easily as a basic ingredient in making organic fertilizer is human urine. Human urine contains several important nutrients needed by plants. The purpose of this research was to know the effect of organic fertilizer on growth and yield of luffa, and also to determine the best consentration. This research used Completely Randomized Design with 5 levels treatment 0, 10%, 20%, 30% and 40%. Each treatment was repeated 4 times, so there were 20 experimental units. The results showed that liquid organic fertilizer affected on the number and weight of luffa fruit. The concentration of liquid organic fertilizer 30% and 40% produce the highest number of fruit, while a concentration of 10% gives the largest fruit weight.